Establishment and Initial Experience of Clinical FLASH Radiotherapy in Canine Cancer Patients - Konradsson, Elise; Arendt, Maja L.; Bastholm Jensen, Kristine; Børresen, Betina; Hansen, Anders E.; Bäck, Sven; Kristensen, Annemarie T.; Munck af Rosenschöld, Per; Ceberg, Crister; Petersson, Kristoffer (Frontiers in Oncology, 2021)
FLASH radiotherapy has emerged as a treatment technique with great potential to increase the differential effect between normal tissue toxicity and tumor response compared to conventional radiotherapy. To evaluate the feasibility of FLASH radiotherapy in a relevant clinical setting, we have commenced a feasibility and safety study of FLASH radiotherapy in canine cancer patients with spontaneous superficial solid tumors or microscopic residual disease, using the electron beam of our modified clinical linear accelerator. The setup for FLASH radiotherapy was established using a short electron applicator with a nominal source-to-surface distance of 70 cm and custom-made Cerrobend blocks for collimation. The beam was characterized by measuring dose profiles and depth dose curves for various field sizes. Ten canine cancer patients were included in this initial study; seven patients with nine solid superficial tumors and three patients with microscopic disease. The administered dose ranged from 15 to 35 Gy. To ensure correct delivery of the prescribed dose, film measurements were performed prior to and during treatment, and a Farmer-type ion-chamber was used for monitoring. Treatments were found to be feasible, with partial response, complete response or stable disease recorded in 11/13 irradiated tumors. Adverse events observed at follow-up ranging from 3-6 months were mild and consisted of local alopecia, leukotricia, dry desquamation, mild erythema or swelling. One patient receiving a 35 Gy dose to the nasal planum, had a grade 3 skin adverse event. Dosimetric procedures, safety and an efficient clinical workflow for FLASH-RT was established. The experience from this initial study will be used as a basis for a veterinary phase I/II clinical trial with more specific patient inclusion selection, and subsequently for human trials.